The influence of sensory information on two-component coordination during quiet stance - Zhang, Yuanfen; Kiemel, Tim; Jeka, John (Gait & posture, 2007)
When standing quietly, human upright stance is typically approximated as a single segment inverted pendulum. In contrast, investigations, which perturb upright stance with support, surface translations or visual driving stimuli have shown that the body behaves like a two-segment pendulum, displaying both in-phase and anti-phase patterns between the upper and lower body. We have recently shown that these patterns co-exist during quiet stance; in-phase and anti-phase for frequencies below and above 1 Hz, respectively. Here we investigated whether the characteristics of these basic patterns were influenced by the addition or removal of sensory information. Ten healthy young subjects stood upright on a rigid platform with different combinations of sensory information: eyes were open or closed with or without light touch contact (<1 N) of the right index fingertip with a 5 cm diameter rigid force plate. The in-phase and anti-phase pattern co-exist in both the anterior-posterior (AP) and medial-lateral (ML) directions of sway. The real part of trunk-leg complex coherence decreased with the addition of vision and light touch, corresponding to a transition from the in-phase to anti-phase pattern at a lower frequency. In the AP direction, the decrease was only observed at frequencies below 1 Hz where the in-phase pattern predominates. Additional sensory information had no observable effect at sway frequencies above 1 Hz, where the anti-phase pattern predominates. Both patterns are clearly the result of a double-linked inverted pendulum dynamics, but the coherence of the in-phase pattern is more susceptible to modulation by sensory information than the anti-phase pattern.